Concomitant of Pulmonary Hydatid Cyst and Aspergilloma: A Rare Coinfection - Zahra Zareshahrabadi; Bahador Sarkari; Nadereh Shamsolvaezin; Bizhan Ziaian; Alireza Tootoonchi; Reza Shahriarirad; Kamiar Zomorodian (Case Reports in Infectious Diseases)
The coexistence of cystic echinococcosis (CE) and aspergilloma is rather uncommon. Aspergillus species, saprophytic fungi, can colonize pulmonary cavities that are caused by tuberculosis, sarcoidosis, and CE. Infection by Aspergillus is often occurring in immunosuppressed patients. However, coinfection of aspergilloma with pulmonary hydatid cyst is very unusual, especially in an immunocompetent patient with unruptured cyst. Herein, we report a case of lung hydatid cyst coinfected with Aspergillus in a 42-year-old Iranian man from Southern Iran. Chest X-ray and computed tomography (CT) scan showed a circumscribed cystic lesion in the superior and inferior segment of the lower lobes of right and left lungs that suggests hydatid cyst. Radical surgery (lobectomy) was performed for the patient. Histopathological evaluation reconfirmed the classical laminated layer of hydatid cyst. Moreover, the ectocyst layer of the right lung showed the presence of numerous cluster septate hyphae with acute-angled branching, as seen in the morphology of Aspergillus species. DNA was extracted from the cyst, and the ITS1-5.8s-ITS2 region of the fungal agent was amplified. Sequencing and analysis of seminested PCR product revealed that the isolate has the most similarity with Aspergillus niger. Further attention is recommended to control fungal pathogens during pulmonary hydatidosis. The coexistence of aspergilloma should always be kept in mind for the better management of CE.